One-eyed cat - Fox, Paula (New York : Bantam Doubleday Dell Books for Young Readers, 1985)
An eleven-year-old shoots a stray cat with his new air rifle, subsequently suffers from guilt, and eventually assumes responsibility for it.
Elem. School Library Collection.
Wilson's Children.
Wilson's Junior High School.
Book Links (A.L.A.), September 1999.
Booklist, October 2005.
Child Study Children's Book Committee, April 2006.
Keywords: Cats -- Fiction; Firearms -- Fiction; Cats -- Fiction; Firearms -- Fiction